ZIKA virus infection and congenital Zika syndrome: A systematic review - Czyz, Witold; Stojak, Łukasz; Baczewski, Mateusz; Urbańska, Karina; Popiela, Dariusz; Kwiatkowski, Filip; Grego, Mateusz; Grego, Katarzyna (Journal of Education, Health and Sport, 2025)
Zika virus (ZIKV), studied since 1950s and known for occasionally causing a mild, febrile illness in humans, became a public health emergency and a global threat to health, with its most recent major outbreak, in Brazil (2015-2016), declared a Public Health Emergency of International Concern by the WHO. This literature review aims to provide a short summary of the research and current knowledge about ZIKV, its epidemiology and the associated medical conditions, with a particular focus on fetal and neonatal microcephaly.